Examining the Impact of Social Influence and Price Sensitivity on Purchase Intention - Dyah Ratu Dwihapsari; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research investigates how social influence and price sensitivity affect consumers’ purchase intentions within Indonesia’s e-commerce environment by applying the Stimulus–Organism–Response (S–O–R) model. In this conceptual framework, social influence and price sensitivity function as external stimuli, perceived value acts as the internal cognitive evaluation process, and purchase intention represents the resulting behavioral outcome. The study utilized a quantitative approach with a cross-sectional design, gathering data from 115 Indonesian consumers who actively engage in online shopping through a structured questionnaire. To assess the relationships among the variables, multiple regression analysis was conducted to evaluate both direct and mediated effects. The findings indicate that social influence and price sensitivity significantly and positively contribute to perceived value. Furthermore, perceived value demonstrates a substantial positive impact on purchase intention. The analysis also shows that social influence and price sensitivity directly influence purchase intention, suggesting that perceived value serves as a partial mediator in these associations. Overall, the results highlight that consumers’ intentions to purchase are driven not only by rational value assessments but also by immediate responses to social signals and pricing considerations.